Roles for Alexithymia, Emotion Dysregulation and Personality Features in Gambling Disorder: A Network Analysis - Mestre-Bach, Gemma; Granero, Roser; Fernández-Aranda, Fernando; Potenza, Marc N.; Jiménez-Murcia, Susana (Journal of Gambling Studies, 2023)
Although there is a growing interest in exploring the specific role of both emotional regulation processes and alexithymia in gambling disorder (GD), evidence remains scarce. In order to delve deeper into the complex interactions between these factors, the present study aimed at exploring a network of the core GD-related features, including GD symptomatology and severity, emotion dysregulation, alexithymia, and personality features. The sample included N = 739 treatment-seeking patients with GD (691 men and 48 women), aged 18–78 years (mean age = 39.2, SD = 13.2). The DSM-5 diagnostic criteria were assessed in, and the South Oaks Gambling Screen, Difficulties in Emotion Regulation Scale (DERS), and Temperament and Character Inventory-Revised were administered to, participants. A network analysis was conducted to reveal inter-relationships between these elements. Three nodes related to emotion dysregulation showed the most critical position in the whole network of the present study: “lack of emotional awareness”, “non-acceptance of emotional responses”, and “difficulties engaging in goal-directed behaviors”. When analyzing emotional dysregulation using the different DERS subscales, two independent clusters were identified. One cluster encompassed alexithymia dimensions (“lack of awareness” and “lack of clarity”), while the other cluster included all other emotion-dysregulation dimensions. Identification of the emotion-dysregulation- and GD-related features with the highest centrality/linkage may be particularly useful for developing valid measurement tools and precise management plans for individuals with GD.
Keywords: alexithymia; emotion regulation; gambling disorder; personality; Scopus; JCR